Digital Horizons in Maritime Education: Navigating Challenges and Perspectives at STIP Jakarta - Marudut Bernadtua Simanjuntak (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research investigates the integration of digitalization challenges in maritime education, focusing on 240 cadets at the Maritime Institute Jakarta (STIP Jakarta). In their pivotal third semester, cadets undergo comprehensive preparation for internships, aligning with their majors—Nautical, Technical, and Port and Shipping Management. The study, adopting a qualitative descriptive approach, delves into cadets' perspectives on